Design of Multiplier-less FIR filters with Simultaneously Variable Bandwidth and Fractional Delay - Aravind Illa (Engineering Science and Technology, an International Journal, 2016)
Low complexity and reconfigurability are the key features in emerging communication applications in order to support multi-standards and operation modes. To obtain these features, an efficient implementation of finite impulse response (FIR) filter, with Variable Bandwidth and Fractional Delay, is proposed in this paper. The reduction in the implementation complexity is achieved by converting the continuous filter coefficients to signed power of two (SPT) space. This may lead to performance degradation. Hence, in this paper, Artificial Bee Colony (ABC) optimization is deployed for finding the near optimal solution in the discrete space.